Peranan Manajemen Pengawasan, Komitmen, Perencanaan dan Kemampuan Karyawan - Nur Aurellia Marta Lerifka Maharani; Sungkono S (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In a company it is very crucial to have supervisory management who is authorized to supervise the operational activities of a company. Which later becomes a benchmark whether a company is good or not. Supervisory management is no less important, it needs its role in the company, in which the majority ownership of the company is owned by the state. For this reason, for companies to be able to contribute, good corporate governance is needed. Included in terms of employee enthusiasm at work, planning, employee capabilities. This article reviews supervisory management planning: commitment, planning, employee capabilities that affect supervisory management, namely: a literature study on human resource management. The purpose of writing this article is to hypothesize the influence between variables to be used in further research. The results of this literature review article are that commitment influences supervisory management, planning influences supervisory management, and employee abilities influence supervisory management.